Предмет: Алгебра,
автор: Itory
1. Решите уравнение с помощью замены переменной
3^(x+1)+18*3^(-x)=29
2. Решите уравнения, приводя к одному основанию
а) 2√x-3=4
б) ^5√7x+1=49/√7
Ответы
Автор ответа:
0
3^x·3 +18/3^x = 29 | ·3^x = t
3t² +18 = 29 t
3 t² - 29 t +18 = 0
D = b²-4ac = 841 - 216 = 625
t1 = (29+25)/6 = 54/6 = 9
t2 = (29 - 25)/6 = 4/6 = 2/3
a) 3^x = 9 б) 3^x = 2/3
x = 2 x lg3 = lg2 - lg3
x = (lg2 - lg3)/lg3
2√x - 3 = 4 |²
4(x - 3) = 16
4x -12 = 16
4x = 28
x = 7
3t² +18 = 29 t
3 t² - 29 t +18 = 0
D = b²-4ac = 841 - 216 = 625
t1 = (29+25)/6 = 54/6 = 9
t2 = (29 - 25)/6 = 4/6 = 2/3
a) 3^x = 9 б) 3^x = 2/3
x = 2 x lg3 = lg2 - lg3
x = (lg2 - lg3)/lg3
2√x - 3 = 4 |²
4(x - 3) = 16
4x -12 = 16
4x = 28
x = 7
Похожие вопросы
Предмет: Алгебра,
автор: aleksandra071228
Предмет: Математика,
автор: timofeimordasov942
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: avnas84
Предмет: Алгебра,
автор: 23настя